Effects of storage conditions and pre-chilling periods on germinability of Pinus ponderosa seeds from Patagonia, Argentina: preliminary study - Pasquini, Nora Mariela; Defossé, Guillermo Emilio (BOSQUE, 2017)
In Argentinean Patagonia, ponderosa pine seeds (Pinus ponderosa) are collected in good production years, stored at ambient conditions, and used thereafter for seedling production. However, information about the effects of conditions and periods of storage on seed quality is scarce. The objectives of this study were: a) to evaluate germination percentage (GP) and germination energy (GE), of ponderosa pine seeds recently collected, and after three and four years of storage in plastic boxes at ambient conditions, and b) to determine if different pre-chilling periods might influence GP and GE as a function of storage time. Part of a seed lot, collected in 2000 in a mesic site near the town of Trevelin in Patagonia, was used to determine moisture content, GP and GE (using 21-days pre-chilling). Another part of that seed lot, stored at ambient conditions for three and four years, was subjected to pre-chilling for 21, 40 and 60 days. Following 21-days pre-chilling, GE was 34 % and 14 % after three and four years of storage, respectively. Pre-chilling periods of 40 and 60 days increased GE to 62 % and 59 % for seeds stored for three and four years, respectively. GP was maintained at ca 69 % over the four years of storage with a seed moisture content of 7 %. Patagonian nurseries could store their own harvested seed under the conditions established in this study without significant loss of seed viability.